Penamaan Coffee Shop di Kintamani, Bali: Kajian Lanskap Linguistik: Naming Coffee Shops in Kintamani, Bali: A Linguistic Landscape Study - Sutrisna, I Putu Gede; Gena, Engel Bertha Halena; Pramesti, Putu Dewi Merlyna Yuda (Information Technology and Science(ITScience), 2025)
This study examines the linguistic landscape of coffee shop naming in Kintamani, Bali. This area is a strategic tourism area that is experiencing rapid development, marked by the proliferation of coffee shops that use various languages ??in their names. Research on the linguistic landscape in Kintamani Bali is needed to reveal the naming patterns of coffee shops that are mushrooming in the area. The results of this study show the effectiveness of the policies of the Balinese and Indonesian provincial governments regarding the use of language in public spaces. The purpose of this study is to describe the pattern of language use based on the categories of monolingual, bilingual, and multilingual, analyze the syntactic patterns of phrases used, and identify the informational and symbolic functions of the naming. To achieve the above research objectives, the researcher used a qualitative descriptive method. Data collection techniques in this study were through observation, documentation, and visual recording. The results showed that English dominates the naming of coffee shops, followed by Indonesian and other foreign languages ??such as Spanish, Italian, and Japanese. Naming patterns are monolingual, bilingual, and multilingual. Phrase patterns in coffee shop naming with a dominant Explaining-Explaining (MD) pattern. The function of naming is not only informative but also symbolic, reflecting identity, aesthetics, and branding strategies in the context of globalization and locality. The dominance of English and the variety of forms and functions of naming indicate a business communication strategy that is responsive to the tourism market while also reflecting linguistic practices in a multilingual public space.